ANALISIS KESULITAN GURU BAHASA INDONESIA DALAM PENERAPAN PEMBELAJARAN HIGHER ORDER THINKING SKILLS (HOTS) DI SMK SWASTA PARIWISATA PRIMA SIDIKALANG - posma sianturi (Jurnal Bahastra, 2021)
ABSTRACT This study aims to determine the Analysis of the Difficulties of Indonesian Language Teachers in Learning Higher Order Thinking Skills (HOTS) at Prima Sidikalang Tourism Private Vocational School. The problem of learning difficulties in HOTS learning is described based on two aspects which include teacher difficulty factors seen from intelligence and teacher difficulty factors seen from teacher non-intelligence in Indonesian language learning. The population of this study were teachers and students at the Prima Sidikalang Tourism Private Vocational School who implemented HOTS-based learning.The results showed, informants were not ready or had difficulty implementing HOTS-based learning. In the aspect of implementing learning, the teacher still does not fully understand about K13 so that it makes informants still have difficulty in determining the learning model used in the learning that is delivered. The results of research conducted by researchers also show that HOTS-based learning is still not well understood in HOTS learning, HOTS-oriented lesson plans preparation, preparation of questions or HOTS-based questions or in an assessment format in HOTS-based learning.Key words: Teacher Difficulties, HOTS-Based Learning, Indonesian Language Education